Incidencia de Escherichia coli y Salmonella spp. en carne cruda de pollo que se expende en el cantón Bolívar - Peralta Vera, Andrea Isabel (2025)
The study aimed to identify the presence of Escherichia coli and Salmonella spp. in raw chicken meat sold in the Bolívar canton. A total of 57 samples were collected, distributed as 43 from the Calceta parish, 10 from Membrillo, and 4 from Quiroga, which were processed at the Microbiology Laboratory of the Veterinary Medicine program at ESPAM-MFL, using selective media cultures Salmonella-Shigella BBL™ and MacConkey, following the protocols established in the INEN 1529-15 standard. The results showed a high microbial load, as 100% of the samples tested positive for E. coli, with values far exceeding the permissible limit of 1.0 × 10² CFU/g; the most critical scenario was recorded in Membrillo, with an average of 4.3 × 10⁶ CFU/g. As for Salmonella spp., it was detected in 75% of the total samples collected in Bolívar canton, with a distribution of 90% in Membrillo, 79% in Calceta, and 0% in Quiroga, confirming a high prevalence in the area. Surveys conducted with vendors revealed practices that favor contamination, such as the lack of refrigeration during transportation, limited knowledge of the slaughtering process, and the almost immediate sale of poultry meat after slaughter. Altogether, these findings indicate that much of the chicken meat marketed in Bolívar canton does not comply with established microbiological standards, posing a serious risk to public health.